Penerjemahan Surat Diplomatik antara Kerajaan Banten dan Pemerintah Hindia Belanda Tahun 1682: Sebuah Studi Mengenai Paleografi - Megasari, Meyrina (Kementerian Sekretariat Negara Republik Indonesia, 2019)
The study aims to identify the problems in translating Banten diplomatik letter fom Governor of Dutch East Indies to Sulatan Banten on May 1st, 1682 written in Mid-Dutch Paleography. Moreover, the diplomatik letter is considered indirectly translated without comparing the ancient letter to Modern-Dutch. The research methodology uses textual reading using Ancient letter and comparison between Mid-Dutch and Modern-Dutch. As the result, Ancient letter and Mid-Dutch have to be translated first into Modern-Dutch. Therefore, the translator must master Mid-Dutch in identifying each word in the text. Keywords : Diplomatic Letter; Paleography; Mid-Dutch; Modern-Dutch.